2023
DOI: 10.3390/microorganisms11082083
|View full text |Cite
|
Sign up to set email alerts
|

Migraine as a Disease Associated with Dysbiosis and Possible Therapy with Fecal Microbiota Transplantation

Abstract: Migraine is a painful neurological condition characterized by severe pain on one or both sides of the head. It may be linked to changes in the gut microbiota, which are influenced by antibiotic use and other factors. Dysbiosis, which develops and persists as a result of earlier antibiotic therapy, changes the composition of the intestinal flora, and can lead to the development of various diseases such as metabolic disorders, obesity, hematological malignancies, neurological or behavioral disorders, and migrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…FMT is the transfer of gut microbiota from healthy individuals to patients with gut microbiota disorders, achieving the goal of rebuilding the homeostasis and diversity of the gut microbiota ( Bian et al., 2022 ). In recent years, FMT has shown specific therapeutic effects in diseases such as migraine ( Kappéter et al., 2023 ), CKD ( Liu et al., 2022 ), and Clostridium difficile infection ( Wei et al., 2022 ). After FMT, DN mice showed significant relief of glomerulosclerosis and fibrosis, glomerular injury, basement membrane thickening, and mesangial proliferation, indicating that reconstruction of normal gut microbiota can alleviate DN.…”
Section: Gut Microbiota and Microbial Metabolites As Therapeutic Stra...mentioning
confidence: 99%
“…FMT is the transfer of gut microbiota from healthy individuals to patients with gut microbiota disorders, achieving the goal of rebuilding the homeostasis and diversity of the gut microbiota ( Bian et al., 2022 ). In recent years, FMT has shown specific therapeutic effects in diseases such as migraine ( Kappéter et al., 2023 ), CKD ( Liu et al., 2022 ), and Clostridium difficile infection ( Wei et al., 2022 ). After FMT, DN mice showed significant relief of glomerulosclerosis and fibrosis, glomerular injury, basement membrane thickening, and mesangial proliferation, indicating that reconstruction of normal gut microbiota can alleviate DN.…”
Section: Gut Microbiota and Microbial Metabolites As Therapeutic Stra...mentioning
confidence: 99%
“…The microbiota influences many systems and organs in the human body, including the brain. In migraine pathophysiology, the gut-brain axis plays an important role and gut microbiota are crucial in modulating this link, but the exact mechanisms are unclear [85,86]. This connection suggests that modulating the microbiota could play a significant role in migraine treatment and represents a promising research area [85].…”
Section: Migraine the Gut-brain Axis And Irritable Bowel Syndromementioning
confidence: 99%
“…The gut microbiota, which includes Bacteroides and Firmicutes, is a complex, dynamic system influenced by diet, lifestyle, infections, antibiotic therapy, and hormones [85]. In addition, early life experiences, such as delivery and breastfeeding, are crucial for the development of this complex system [89].…”
Section: Migraine the Gut-brain Axis And Irritable Bowel Syndromementioning
confidence: 99%
See 1 more Smart Citation

Migraine Comorbidities

Cuciureanu,
Bistriceanu,
Vulpoi
et al. 2024
Life
“…The use of probiotics as dietary supplements may reduce the frequency and severity of migraine attacks, For instance, a study found that an IgG elimination diet combined with probiotics reduced migraine attack frequency in individuals with migraine and irritable bowel syndrome ( Xie et al., 2019 ). Fecal microbiota transplantation represents a promising approach to treating migraine ( Kappéter et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%